Tandem Cyclization of a Bispyridinium Chloride: Facile Synthesis of Substituted Indolizines - Costa, Marta; Noro, Jennifer; Brito, Alexandra; Proença, Fernanda (Synlett, 2013)
Functionalized indolizines were prepared by a one-pot cascade reaction from bispyridinium salts. This mild experimental procedure allowed the isolation of the product in very good yield. Combination of the indolizine derivative with electrophiles confirmed the reactivity of the C3 ring carbon and allowed the bromination, formylation, hydroxymethylation, and dimerization of the indolizine scaffold.
Keywords: pyridinium salt; bispyridinium salt; intramolecular cyclization; indolizines; electrophilic aromatic substitution